1986
DOI: 10.1182/blood.v67.6.1705.bloodjournal6761705
|View full text |Cite
|
Sign up to set email alerts
|

Etiologic aspects of cold agglutinin disease: evidence for cytogenetically defined clones of lymphoid cells and the demonstration that an anti-Pr cold autoantibody is derived from a chromosomally aberrant B cell clone

Abstract: This study investigated the clonal nature of cold agglutinin disease in a series of nine patients, which included the benign or idiopathic form as well as cases with an underlying lymphoma. Surface marker phenotyping and karyotypic analysis were performed on peripheral blood lymphocytes. An increased proportion of B cells was found in four cases and in three of these patients a monoclonal B cell population was identified with a mu, kappa phenotype. In the same three cases, as well as an additional patient, an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
7
1

Year Published

2001
2001
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 0 publications
0
7
1
Order By: Relevance
“…Contrary to the conclusions from earlier investigations (Crisp & Pruzanski, 1982) nearly all patients with ‘primary’ CAD have a lymphoproliferative bone marrow disease, and the monoclonal CAs are produced directly by the neoplastic B cells (Silberstein et al , 1986; Silberstein, 1994; Berentsen et al , 1997). Clonal lymphoproliferation is usually demonstrated by flowcytometric immunophenotyping (Silberstein et al , 1986; Berentsen et al , 1997). Diagnostic histological features are identified in at least half of the patients, most often the features of lymphoplasmacytic lymphoma (Berentsen et al , 1997).…”
contrasting
confidence: 73%
See 1 more Smart Citation
“…Contrary to the conclusions from earlier investigations (Crisp & Pruzanski, 1982) nearly all patients with ‘primary’ CAD have a lymphoproliferative bone marrow disease, and the monoclonal CAs are produced directly by the neoplastic B cells (Silberstein et al , 1986; Silberstein, 1994; Berentsen et al , 1997). Clonal lymphoproliferation is usually demonstrated by flowcytometric immunophenotyping (Silberstein et al , 1986; Berentsen et al , 1997). Diagnostic histological features are identified in at least half of the patients, most often the features of lymphoplasmacytic lymphoma (Berentsen et al , 1997).…”
contrasting
confidence: 73%
“…Diagnostic histological features are identified in at least half of the patients, most often the features of lymphoplasmacytic lymphoma (Berentsen et al , 1997). The clonal B cells nearly always express the CD20 + κ + immunophenotype (Berentsen et al , 1997), and trisomy of the q arm of chromosome 3 has been shown in some cases (Silberstein et al , 1986; Michaux et al , 1998).…”
mentioning
confidence: 99%
“…More recently, it has been possible to verify such cell clones directly. Flow cytometric investigations by Silberstein and co-workers disclosed B-cell clones in at least some patients [ 51 ]. In 1995, we reported the findings of lymphoplasmacytic lymphoma in the bone marrow of three consecutive patients otherwise classified as having primary CAD [ 52 ].…”
Section: Clonal B-lymphocytes In Primary Cadmentioning
confidence: 99%
“…Studies in animal and human AIHA suggested that loss of immunological tolerance to RBC self-antigens might originate by different, nonmutually exclusive mechanisms that include antigenic mimicry, apoptosis, and immunoregulatory disorders including cytokine network alteration. It was found that IgM autoantibodies or cold agglutinins generally react with polysaccharide antigens on the RBC surface and are usually associated with neoplastic B-cell populations [ 92 , 93 ]. By contrast, IgG warm autoantibodies generally react with protein antigens on the erythrocyte surface and are typically panagglutinins, reacting with all cells [ 94 ]; immunoblotting studies implicated Rh antigens, membrane protein band 4.1, protein band 3, and glycophorin A as universal RBC targets.…”
Section: Pathogenesis Of Autoimmunitymentioning
confidence: 99%